Integral Backstepping Controller for an Underactuated X4-AUV - Zainah, Md. Zain; Nurfadzillah, Harun (2016)
The autonomous underwater vehicle (AUV) capability has great important tasks for navigating into abyssal zones and dangerous underwater mission. Mostly AUV has six degrees of freedom (DOF) in motion and is classified in an underactuated system. The underactuated system is a system with fewer inputs than DOF. However, stabilizing an underactuated system is difficult tasks because of the nonlinear dynamic and model uncertainties. Thus, our aim is to obtain control algorithms using Integral Backstepping approach in order to stabilize the X4-AUV. The key idea of Integral Backstepping is to design a virtual controller by working together with the integration of tracking error. Numerical simulation results are given to show the validity and the good performances of the proposed method.